The Islamic Education in the Perspective of Surah At-Tawbah Verse 122: Lessons and Wisdom - Nawirul Huda; Muhammad Yahya Abdullah yahya; Atilla Afynanda Ezar Romdloni Atilla (CV. Kayaswara, 2025)
This article discusses the values of Islamic education contained in Surah At-Taubah verse 122, which are relevant in shaping individuals and society based on scientific and moral principles. This verse emphasises the importance of tafaqquh fiddin (deepening religious knowledge) as the main element of Islamic education. The education reflected in this verse is not only orientated towards theoretical knowledge but also includes integral spiritual, moral and social aspects. This is proven by the many commentators who research and study this verse. Every verse mentioned in the Qur'an has significant meaning and values, and the values contained are learning and education for human life. The aim of this research is to find out the educational values contained in at-Taubah verse 122. The method used in writing this journal is the descriptive analysis method, namely analyzing the problem to be discussed by collecting library data, opinion of the commentators. Then describe the opinions of the commentators, then create conclusion. The results of the research show that the values of Islamic education contained in Surah At-Taubah verse 122 are: 1). Deep Understanding of Religion. 2). Continuing Education. 3). Da'wah duties. 4). Security Awareness and Precautions. 5). Consideration in Action.